Numerical simulation of atomic positions in quantum dot by means of molecular statics - Dłużewski, P.; Traczykowski, P. (Archives of Mechanics, 2003)
Deformation of a crystal structure is considered here in terms of constitutive modelling based upon both the atomistic and continuum approaches. Atomistic calculations are made by using the Stillinger-Weber potential for the GaAs and CdTe structures. The stress-strain behaviour of the best-known anisotropic hyperelastic models are compared with the behaviour of the atomistic one in the uniaxial deformation test.